Growth hormone effect on body composition of children born small for gestational age: a systematic review - Adriana M. Kühl; Catiuscie C.S. Tortorella; Claudia C.B. Almeida; Marcia R.M. Gomes Dias; Rosana M. Pereira (Elsevier, 2023)
Objective: The present study aimed to evaluate the effects of GH treatment on the body composition of children born with SGA. Methods: This study is a systematic review of the literature. CINAHL, Embase; Medline/Pubmed, Scopus and Web of Science were searched from inception to March 2022. Results: Four studies met the inclusion criteria, with an intervention time of 1 to 3 years, using doses from 0.03 to 0.07 mg/kg/day of GH. Bone densitometry by dual-energy X-ray absorptiometry (DXA) with whole-body scans was the most used method to assess body composition. Most studies (n = 3) had SGA children as a control group with the same characteristics as the case group; the mean age was similar between the groups (minimum of 5.1 ± 1.4 years and maximum of 6.7 ± 1 0.8 years) and all participants had an average height ≤ -3DP. The Lean Mass (LM) and Fat Mass (FM) outcomes of the studies were not presented in a standardized manner; thus, they cannot be compared. There was a significant increase in LM in the group treated with GH in relation to the pre-treatment period and in comparison, to the untreated control group. Three studies showed a significant decrease in FM at the end of the intervention period, and in two studies, this decrease occurred in the control group. Conclusions: Despite the differences in the presentation of results and in the evaluation periods, the results of the studies showed that growth hormone favors the gain and maintenance of lean mass, and it also affects fat mass reduction and redistribution.